2022
DOI: 10.1007/s00383-022-05064-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of infantile hydrocele in pediatric age group

Abstract: Purpose To evaluate laparoscopic management of hydroceles in pediatrics, with evaluation of the internal inguinal ring (IIR) and the PPV (patent processus vaginalis) in different types of hydroceles, and the incidence of the contralateral PPV. Methods The IIR and the type of hydrocele on the same side of 93 patients with 106 infantile hydroceles were evaluated and managed, in addition to contralateral side. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(38 reference statements)
1
5
0
1
Order By: Relevance
“…Ahmed Elhaddad et al conducted a prospective study of 93 male children with 106 hydroceles in which they found type II hydroceles in 73.6% of cases. Type I was found in only 8.5% and type III in the remaining 17.9% [5]. Our study is consistent with the findings of Choi et al who described an open internal inguinal ring in all cases [39].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ahmed Elhaddad et al conducted a prospective study of 93 male children with 106 hydroceles in which they found type II hydroceles in 73.6% of cases. Type I was found in only 8.5% and type III in the remaining 17.9% [5]. Our study is consistent with the findings of Choi et al who described an open internal inguinal ring in all cases [39].…”
Section: Discussionsupporting
confidence: 92%
“…Congenital patent processus vaginalis, which permits fluid flow between the peritoneal and tunica cavities, is the primary cause of hydrocele in children. The frequency is about 5.7% [5]. These hydroceles often disappear spontaneously in 18 to 24 months [6].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the diseases in the inguinal scrotum are quite complicated, including many interwoven diseases, such as hydrocele, often associated with inguinal hernia, inflammatory diseases, varicocele. Inguinal scrotum region also has anatomical structures with many complex pathological terms, even between the sexes there are separate pathological terms that are difficult to distinguish 1,2 . This article updates a number of issues related to hydrocele, including knowledge of anatomy, embryology, classification, etiology, clinical manifestations, imaging findings, and management.…”
mentioning
confidence: 99%
“…Inguinal scrotum region also has anatomical structures with many complex pathological terms, even between the sexes there are separate pathological terms that are difficult to distinguish. 1,2 This article updates a number of issues related to hydrocele, including knowledge of anatomy, embryology, classification, etiology, clinical manifestations, imaging findings, and management.…”
mentioning
confidence: 99%